Hospital pharmacists working with geriatric patients in Europe: a systematic literature review - Kiesel, Esther (Eur J Hosp Pharm, 2018)
OBJECTIVES: Multimorbidity of geriatric patients often leads to polypharmacy that increases the risk for drug interactions. Geriatric patients are also more sensitive to adverse drug reactions due to physiological changes resulting from ageing. Hence, the use of medicines should be considered thoroughly. This systematic literature review aimed at identifying and presenting available evidence on the effect of pharmaceutical interventions on geriatric patients, their medications or healthcare costs in a clinical setting in Europe. METHODS: We included all studies on research of pharmaceutical interventions on geriatric inpatients (≥65 years) in Europe since 2001. Database searches were conducted on PubMed, EMBASE, The Cochrane Library and AgeInfo. In addition, the following journals were searched manually: European Journal of Hospital Pharmacy, ‘Krankenhauspharmazie’, ‘Medizinische Monatsschrift für Pharmazeuten’ and ‘Zeitschrift für Gerontologie und Geriatrie’. RESULTS: Database screening yielded 8058 hits. After deletion of duplicates, screening of title and abstract, 143 full-text articles were analysed and 17 papers were included. Manual searching added four more papers. Included studies were conducted in Belgium, Denmark, England, Ireland, the Netherlands, Sweden and Spain. They demonstrate that pharmaceutical care on wards leads to more appropriate medication use and might reduce outcomes like drug-related readmissions. Intensified pharmaceutical care showed additional effects, even in countries with established pharmaceutical care in hospitals. CONCLUSIONS: This systematic literature review demonstrates that ward-based pharmacists may improve the appropriateness of medications, seamless care and drug safety for geriatric inpatients while being cost effective.